APPLICATION OF THE SYLLABLE READING METHOD FOR IMPROVING STUDENTS' READING ABILITY IN LEARNING INDONESIAN LANGUAGE IN CLASS I STATE STATE 35 PRIVATE SCHOOL 35 TRANS SATA KAYONG UTARA DISTRICT - Hastuti, Dwi; Azmi , Ulil (Journal of Learning on History and Social Sciences, 2023)
This research was carried out because in the delivery of material by the teacher, students did not understand it. This has an impact on students' low reading abilities, resulting in low student learning outcomes. This is because the delivery of the material is not supported by appropriate learning media, inappropriate supporting books, and inappropriate methods. This research is one of the graduation requirements for the PKP course and increases the teacher's ability to design learning using the syllabic reading method, with the aim of increasing students' reading ability and understanding of material as well as increasing the trust of the community around the school. The focus of this research lies in students' reading abilities using the syllabic reading method. Research activities are divided into two cycles with each cycle consisting of one face-to-face meeting. It is hoped that the results of this research can improve students' reading ability and student learning outcomes according to the established Kkm. From the achievement of the results of the student learning process using the syllabic reading method, there has been an increase. This can be seen from cycle one with an average class score of 58 to 84 in cycle two and a percentage of 30% in cycle one to 90% in cycle two.